Personality and Resilience as Determinants of Psychological Well-being among Military Children - Sharma, Nity; Nagle, Yashwant Kumar (Defence Life Science Journal, 2018)
The military children are a population who are susceptible to psychological stress from the hardships of military life, such as frequent moves and separation from their parents during deployment. Military children are resilient as well as stress prone at the same time. While frequent moves build resilience, combat deployments of their parents makes them vulnerable to the risks associated with psychological and emotional health, attachment problems and coping while overcoming traumatic grief due to death of a family member. The risk is highest right after the military personnel leaves for deployment and immediately upon return. In order to understand the psychological health of children of military personnel, it is important to understand their resilience and personality in relation to psychological well-being. In addition to being a personal trait, resilience is a product of the relationships between children and the resources around them. Despite needs to better understand the impact of deployment on military children and families and to provide proper support for them, rigorous research is deficient. A comprehensive approach based on strengths and problems, of military children and families, with a focus on the prevention, is the need of the hour. The present paper focuses on study of personality and resilience as determinants of psychological well-being. The study was conducted on military children (N= 124) of Army Public School, using HEXACO-PI, Brief Resilience Scale and Psychological Wellbeing Scale. The data was analyzed using descriptive and inferential statistics. Results and implications are discussed in the paper. Issues in need of further research are emphasized, especially research into programs that assist military children and families.